KARYA SASTRA SEBAGAI DOKUMEN SOSIAL DALAM TRILOGI CERPEN PENEMBAK MISTERIUS KARYA SENO GUMIRA AJIDARMA: KAJIAN SOSIOLOGI SASTRA-OBJEKTIF - Suantoko, Suantoko (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2019)
The Seno Gumira Ajidarma short story collected in the Penembak Misterius trilogy is very interesting to read. In addition, as a social document, the collection of short stories can be identified a social setting that actually became a place of social events occurred, the social setting of the Penembak Misterius that occurred during the New Order era in the 1980s. More precisely the social setting created at the party meeting officials in a hotel, the shootings through the night, and the violence of the state apparatus. The social context referred to by Seno Gumira Ajidarma is a mysterious shooting incident known as "petrus" during the New Order period. It is intended to denounce the practice of legal violence from the action of "petrus." As a social document or even a social critique of the New Order rule, the Penembak Misterius trilogy comes as a social relation of literary works to social reality. That is because, the silence of the conscience is very interesting shown by the assassin. When the issue of "Petrus" is about to be removed from the memory of society, this trilogy is present in the public. The presence of the "Petrus" trilogy depicted in not only be seen as a social document but also a lawsuit against social reality in the New Order era.